Sustainability engagement and shariah-compliant mutual funds: a preliminary study - Abd Mutalib, Hafizah; Muhammad Jamil, Che Zuriana; Che Adam, Noriah (American Scientific Publisher, 2018)
Previous studies indicate that mutual funds are profit-oriented transient investors. Therefore, investing in firms with good sustainability engagement is not a good idea for mutual funds as it is seen as cost incurring, hence reducing the profit. However, this study believes that such investment preference is different for the mutual funds which are Shariah-compliant. Based on the Islamic principles of tawhid (faith), khalifah (vicegerent) and ukhuwwah (brotherhood), which suggest close connection between Islam and sustainability, this study examines that firms’ sustainability engagement may have the ability to attract investments from Shariah-compliant mutual funds. The analyses from this study suggest preliminary findings that Shariah-compliant mutual funds do have preference to invest in firms with good sustainability commitments.